Causes and Consequences of Truancy Among in School Adolescents in Oyo North Senatorial District Nigeria - Foluke Nike Bolu Steve; Rasaq Abimbola Fadipe; Olajide Charles Kayode (Universitas Ahmad Dahlan, 2022)
Background: The need to increase the mastery of Information and Computer Technology (ICT) in teaching and learning activities is essential and urgent, especially during the COVID-19 pandemic. The PowerPoint application is a popular application for creating learning content, but most teachers are only at the level of